Analisis Equity Market Timing dan Struktur Modal - Acchedya Anugrahani; Rahmat Setiawan (Universitas Yudharta Pasuruan, 2020)
Abstract This study aims to examine the effect of equity market timing in determining the company's capital structure decisions. The sample used was Indonesian manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2018 period. This study uses independent variables namely market to book ratio and External finance weighted average market to book ratio (EFWAMTB), the dependent variable used is market leverage, and the control variables used are profitability, tangibility, and size. This study uses panel data regression. The results of this study indicate that the MTB ratio and EFWAMTB have a significant negative effect on market leverage. So it can be said that Indonesian manufacturing companies apply the equity market timing theory in determining capital structure decisions. The profitability and firm size control variables give significant negative and the tangibility variable shows significant positive results on the company's market leverage. Keywords: equity market timing, market to book ratio, market to book ratio dan External finance weighted average market to book ratio (EFWAMTB), ROA, tangibility, size and market leverage. Abstrak Penelitian ini bertujuan untuk menguji pengaruh equity market timing dalam menentukan keputusan struktur modal perusahaan.Sampel yang digunakan adalah perusahaan manufaktur Indonesia yang terdaftar di Bursa Efek Indonesia (BEI) periode 2013-2018. Strudi ini menggunakan variabel independen yaitu market to book ratio dan external finance weighted average market to book ratio (EFWAMTB), variabel dependen yang digunakan yaitu market leverage dan variabel kontrol yang digunakan adalah profitabilitas, tangibilitas dan size. Studi ini menggunakan regresi data panel.Hasil penelitian ini menunjukan bahwa MTB dan EFWAMTB berpengaruh negatif signifikan terhadap market leverage.Sehingga dapat dikatakan perusahaan manufaktur Indonesia menerapkan teori equity market timing dalam menentukan keputusan struktur modalnya. Variabel kontrol profitabilitas dan firm size memberikan hasil negatif signifikan dan untuk variabel tangibilitas menunjukan hasil positif signifikan terhadap market leverage prusahaan. Kata Kunci: equity market timing, market to book ratio, market to book ratio dan External finance weighted average market to book ratio (EFWAMTB), ROA, tangibility, size and market leverage